Bahasa Inggris - Saifana, Qanita; Ganta, Ahmad Reza Rafi; Suryandaru, Muhammad Kynan Rafii; Nusantara, Muhammad Radja; Enigo, Muhammad Ricad; Bages, Nouv Aqila (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2025)
Background: Rheumatoid arthritis (RA) is a chronic autoimmune disease that causes pain, stiffness, and joint damage, as well as other systemic symptoms. The prevalence of RA worldwide is around 1-2%. The disease is influenced by genetic and environmental factors such as infection, pollution, and diet. Diet can affect RA symptoms; foods such as red meat, alcohol, and sodas can aggravate, while fish and berries can alleviate symptoms. The Mediterranean diet, which is rich in herbs and olive oil, as well as gluten-free vegetarian and vegan diets, show positive effects on RA. Research suggests that this diet may contribute to the lower prevalence of RA in Southern Europe compared to other regions. Methods: This study used PubMed and Google Scholar as the main databases. Key words were used, such as “Rheumatoid Atritis”, “Diet”. Considering the relevance of the topic under study, the literature selected for inclusion in this paper covered publications from 2019 to 2024. Discussion: The results of this systematic review suggest that anti-inflammatory, Mediterranean, and gluten-free diets may provide benefits in reducing pain and inflammation in adults with RA. The Mediterranean diet in particular has been shown to be effective in improving quality of life and reducing RA disease activity. Conclusion: Dietary management, especially anti-inflammatory, Mediterranean, and gluten-free diets may play an important role in the control of RA symptoms in adults. Recommendations to adopt a healthy and anti-inflammatory diet may be an effective strategy in RA management. Keywords: Rheumatoid Arthritis, Diet